Treatment of Recurrent Vulvovaginal Candidiasis With Ibrexafungerp - Leah M. Grant MD; Robert Orenstein DO (SAGE Publishing, 2022)
Recurrent vulvovaginal candidiasis is a common disorder which causes significant morbidity among women worldwide, and treatment options are limited. Ibrexafungerp is a novel antifungal agent which was approved in 2021 for treatment of vulvovaginal candidiasis. We present a case of recurrent vulvovaginal candidiasis successfully treated with ibrexafungerp.